Nutritional state of scholars from 6 to 11 years old. Clinical-anthropometrical characterization. - Alexander Torres Molina (Medisur)
Background: Nutritional assessment as a methodology allows identifying the nutritional status of individuals or populations, and is based on the assessment of anthropometric, clinical, biochemical and dietary rates. Objective: To evaluate the behaviour of the main anthropometric and nutritional rates as well as the nutritional status of scholars from 6 to 11 years old. Methods: A descriptive and cross-sectional study was conducted from January to June 2010. The sample consisted of 1601 children. The following variables were analyzed: age, sex, current nutritional status, height/age ratio, body mass index according to age and abdominal circumference index, also according to age. Results: 73.1% (1171) of children were of normal weight, 8.6% (138) were obese, 10.5% (168) were overweight and only 3.6% (57) were undernourished. Obesity (11.2%), overweight (12.8%) and malnutrition (4.3%) were predominant in males. In the case of obese and overweight children, they respectively showed a 54.6% and a 36.1% who were over the height average expected for their age and sex. Conclusions: There is a tendency to overweight and obesity in schoolchildren of Moa, as well as a low percentage of malnourished patients. Correlation was observed between the current nutritional status and anthropometric rates that were evaluated. Most obese patients present visceral obesity.